Advanced location-based IPv6 address for the node of wireless sensor network - Hussein, M.N. (Institute of Advanced Engineering and Science, 2020)
Fields such as military, transportation applications, human services, smart cities and many others utilized Wireless Sensor Network (WSN) in their operations. Despite its beneficial use, occurrence of obstacles is inevitable. From the sensed data, the randomly nodes distribution will produce multiple benefits from self-configuration and regular positioning reporting. Lately, localization and tracking issues have received a remarkable attention in WSNs, as accomplishing high localization accuracy when low energy is used, is much needed. In this paper, a new method and standards-compliant scheme according to the incorporation of GPS location data into the IPv6 address of WSN nodes is suggested. The suggestion is likewise others which depends on ground-truth anchor nodes, with a difference of using the network address to deliver the information. The findings from the results revealed that perfect GPS coordinates can be conducted in the IPv6 address as well as with the transmission radius of the node, and the information is significantly adequate to predict a node's location. The location scheme performance is assessed in OMNet++ simulation according to the positioning error and the power metrics used. Moreover, some improvement practices to increase the precision of the node location are suggested. Copyright Â© 2020 Institute of Advanced Engineering and Science. All rights reserved.